A BRIEF SURVEY OF BIOMASS HYDROLYSIS AS A VITAL PROCESS IN BIO-REFINERY - TONGSHUWAR, Geoffrey Timothy; OYEGOKE, Toyese (FUDMA JOURNAL OF SCIENCES, 2021)
This report presents a mini-survey of biomass hydrolysis, which tends to unfold the concept of what the process is all about, categories involved, and reporting concerning the processes involved in each category. The categories entail the chemical and biological means where acid catalysts and enzymes are used, respectively, including reports of some works carried out in the literature.